A Rare Association: Hereditary Hemorrhagic Telangiectasia with Liver Cirrhosis Causing Portal Hypertension - Denisse Morales-Tovar; Froylan D. Martínez-Sánchez; Alejandro Gabutti-Thomas; Rodolfo Rivera-Martínez; Jacqueline Córdova-Gallardo (Case Reports in Gastrointestinal Medicine)
Hereditary hemorrhagic telangiectasia (HHT), also known as Rendu–Osler–Weber syndrome, is a vascular disorder of autosomal dominant etiology. The hallmark clinical feature is the presence of recurrent episodes of epistaxis in patients with vascular malformations and a tendency to bleed. We present the case of a 71-year-old woman who presented to the emergency department with upper gastrointestinal bleeding caused by esophageal varices, in conjunction with gastric angiodysplasias. The presence of oronasopharyngeal telangiectasias and hepatomegaly raised suspicion of HHT. The diagnostic workup confirmed the presence of angiodysplasia in the gastric region, portal arteriovenous malformation, and a pulmonary shunt.